2015
DOI: 10.1175/jamc-d-14-0278.1
|View full text |Cite
|
Sign up to set email alerts
|

A Synoptic Classification of Inflow-Generating Precipitation in the Snowy Mountains, Australia

Abstract: Precipitation falling in the Snowy Mountains region of southeastern Australia provides fuel for hydroelectric power generation and environmental flows along major river systems, as well as critical water resources for agricultural irrigation. A synoptic climatology of daily precipitation that triggers a quantifiable increase in streamflow in the headwater catchments of the Snowy Mountains region is presented for the period 1958-2012. Here, previous synoptic-meteorological studies of the region are extended by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 67 publications
(121 reference statements)
1
48
0
Order By: Relevance
“…Hoy et al 2014;Newton et al 2014a, b;Bettolli et al 2010;Stahl et al 2006). Theobald et al (2015) presents a novel, automated approach to classifying year-around synoptic systems across SEA, building upon previous studies which largely focussed on cool-season precipitation, ; Pook et al 2006;Wright 1989, Fiddes et al 2014. In addition to the widely studied cold front and closed low weather systems, Theobald et al (2015) found a strong emphasis on tropical moisture pathways from oceans to the north-east and north-west of Australia for delivering precipitation to the Snowy Mountains region.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…Hoy et al 2014;Newton et al 2014a, b;Bettolli et al 2010;Stahl et al 2006). Theobald et al (2015) presents a novel, automated approach to classifying year-around synoptic systems across SEA, building upon previous studies which largely focussed on cool-season precipitation, ; Pook et al 2006;Wright 1989, Fiddes et al 2014. In addition to the widely studied cold front and closed low weather systems, Theobald et al (2015) found a strong emphasis on tropical moisture pathways from oceans to the north-east and north-west of Australia for delivering precipitation to the Snowy Mountains region.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Winter and spring are typically the wettest seasons, when precipitation is heavily influenced by the interaction between the prevailing mid-latitude westerly airflow and orographic effects (Chubb et al 2011;Ummenhofer et al 2009b;Cai and Cowan 2008;Pook et al 2006), and frontal and closed low systems dominate. However, Theobald et al (2015) revealed the importance of warm-season precipitation to the generation of inflows, with more than 40% of precipitation days ≥ 10 mm occurring during the warmer months. During these months, inland heat troughs prevail and high intensity precipitation associated with trajectories of warm, moist air from tropical latitudes is common.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations